Environmental History and the Construction of Nature and Landscape: The Case of the 'Landscaping' of the Jutland heath. (1st February 1996) - Olwig, Kenneth
Abstract : It is my thesis that the discipline we now know as environmental history owes a great deal of its impetus to the emergence at the beginning of the 19th century of a socially engaged and environmentally committed interdisciplinary 'proto-discipline'. A material conception of nature was of key importance to this environmental history, and thereby to the historically conscious conservation movement which it set in motion. This concept of nature as thing could, however, be (mis)construed to represent a reification which separates humanity from nature. This reification, as will be seen, was problematic because it bore concealed within it older normative concepts of nature, which came to imply environmental determinism as a natural ideal and the alienation from nature of any form of humanity which violated this ideal. This meant that humanity tended to be counterpoised to nature. There is a consequent need today to 'deconstruct' this concept of nature in order to 're-invent', as it were, a conception of nature which maintains the conservation imperative, but which shifts its focus from things to the dynamics of a society-environment relation in which humanity can take a positive and active role. I exemplify my argument by drawing upon a classic case of the intertwining of environmental transformations and changing conceptions of nature: that of the 'landscaping' of the Jutland heath. Even though this analysis is not about Transylvania, a key factor in it proves to be an arcane bond between bats, vampires and the concept of landscape.